The Effect of Annealing Temperature and KCN Etching on the Photovoltaic Properties of Cu(In,Ga)(S,Se)2 Solar Cells Using Nanoparticles - Duy-Cuong Nguyen; Ken Fukatsu; Keiji Tanimoto; Shigeru Ikeda; Michio Matsumura; Seigo Ito (International Journal of Photoenergy)
Cu(In,Ga)S2 nanoparticles were synthesized by a hot-injection method under a low-vacuum ambience, which were printed and annealed with Se vapor for Cu(In,Ga)(S,Se)2 solar cells. The Cu(In,Ga)S2 nanoparticles were around 14 nm, and the stable ink was obtained by dispersing the nanoparticles in hexanethiol. The crystallinity of the Cu(In,Ga)(S,Se)2 films increased with the increase in annealing temperature. Cu(In,Ga)(S,Se)2 solar cells with KCN etching after annealing showed better photovoltaic properties than KCN etching before annealing and without etching. The best cell was observed at an annealing temperature of C and KCN etching after annealing; the parameters of this cell were a short-circuit photocurrent density of 27.12 mA/cm2, open-circuit voltage of 0.42 V, fill factor of 0.38, and conversion efficiency of 4.3%.